Socio-cultural and cognitive predictors of eating disorder symptoms in young girls. - Bell, C; Cooper, M (2005)
There is some evidence for a relationship between socio-cultural variables and the development of disordered eating or concerns. However, the role of individual cognition in adding to this relationship has not yet been investigated. The current study therefore had two main questions. Firstly, which of the socio-cultural factors investigated (parental, peers and the media) predict girls' eating disorder related symptoms? Secondly, do individuals' cognitions add to this prediction? Thirty-eight girls participated in the study. They completed the Eating Attitudes Test (EAT), Eating Disorder Belief Questionnaire (EDBQ), measures of parental, peer and media influence, and a measure of their awareness and internalisation of societal standards of attractiveness. The results indicated that several of the socio-cultural factors were related to girls' EAT score. The belief that being thinner would make boys like them more was the most significant predictor in the whole sample (and in younger girls). Individual cognitions added significantly to this prediction in the whole sample but not in the younger girls. For older girls, the importance of magazines as a source of information about beauty and ideals was the strongest predictor of EAT score, and their cognitions added significantly to this prediction. It is concluded that peer and media influences are important determinants of girls' eating disorder related symptoms. However, individual cognitions add to this relationship, particularly in older girls. The implications and limitations of the study are discussed.